Implementasi CSR PT. Incasi Raya Pangian sebagai Bentuk Kepedulian kepada Masyarakat Sekitar - Sulistyanto .; M Hudori (JURNAL CITRA WIDYA EDUKASI, 2018)
This study aims to describe the implementation of CSR is actually carried out by PT. Incasi Raya Pangian the relevant stakeholders as a form of social responsibility. The CSR program has been ongoing since the first until now and has provided many benefits to the local community. Based on the problems studied in this research is how the implementation of CSR and the perceived benefits of the program in the public. The study was conducted through qualitative descriptive approach. Data collected on natural conditions, primary and secondary data sources, and data collection techniques used include interviews, documentation, observation, surveys and literature. Results from this study showed that implementation of CSR in the environment surrounding the company provides excellent benefits for the company and surrounding communities. Implementation of CSR carried out in the public has been going pretty well. Surrounding communities are satisfied for what he has given the company, but there are some things that still need improvement in planning and implementation. Positive perception of the CSR programs of social and environmental areas of the company, which is evidenced by the great expectations of the company's CSR programs to be better and wider benefits for the future.